2022
DOI: 10.1111/imm.13564
|View full text |Cite
|
Sign up to set email alerts
|

The immune response as a double‐edged sword: The lesson learnt during the COVID‐19 pandemic

Abstract: The COVID-19 pandemic has represented an unprecedented challenge for the humanity, and scientists around the world provided a huge effort to elucidate critical aspects in the fight against the pathogen, useful in designing public health strategies, vaccines and therapeutic approaches. One of the first pieces of evidence characterizing the SARS-CoV-2 infection has been its breadth of clinical presentation, ranging from asymptomatic to severe/deadly disease, and the indication of the key role played by the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 167 publications
0
7
0
Order By: Relevance
“…At the same time, recent studies have demonstrated that the development of an effective immune response should be balanced, implying the simultaneous concordant release of both pro- and anti-inflammatory cytokines [ 5 ]. An unbalanced release of proinflammatory cytokines may lead to a “cytokine storm” [ 2 ] similar to the cytokine storm in COVID-19 infection [ 6 ]. A systemic inflammatory reaction (acute or chronic) limits the resolution of inflammation and causes disease progression and tissue damage, affecting all organs and systems of the host body [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, recent studies have demonstrated that the development of an effective immune response should be balanced, implying the simultaneous concordant release of both pro- and anti-inflammatory cytokines [ 5 ]. An unbalanced release of proinflammatory cytokines may lead to a “cytokine storm” [ 2 ] similar to the cytokine storm in COVID-19 infection [ 6 ]. A systemic inflammatory reaction (acute or chronic) limits the resolution of inflammation and causes disease progression and tissue damage, affecting all organs and systems of the host body [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells, von Willebrand/ADAMTS13 axis, coagulation factors, fibrinolytic system, immunothrombosis, inflammatory cytokines, and anti-phospholipid antibodies are all involved in its determination [ 5 ]. We can just hypothesize a possible protective role of vaccination through an action on the immune system, modulating the inflammation-coagulation interface [ 6 ]. The hypothesis of a possible protective role of vaccination in preventing PE in hospitalized COVID-19 patients has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Flaviviruses, Filoviruses, SARS-CoV-2, etc.) is the role of early uncontrolled cytokine storm as the main driver of tissue damage, leading to immune-mediated multi-organ injury and disease progression (7)(8)(9)(10). In this scenario, we could speculate that immunosuppression could paradoxically have a beneficial effect, dampening the excessive inflammatory response and reducing the immune-mediated damage (11).…”
Section: The Immune Response In Ic Patients: a Complex Scenariomentioning
confidence: 99%